Integrated Nutrient Management for Enhancing the Soil Health, Yield and Quality of Little Millet (Panicum sumatrense) - Rani, Y. Sandhya; Triveni, U.; Patro, T. S. S. K. (International Journal of Bio-resource and Stress Management, 2023)
Integrated nutrient management is an approach for management of plant nutrients for maintaining and enhancing soil health, where both natural and man made sources of plant nutrients are used.A field experiment was conducted in little millet during Kharif 2015 at Agricultural Research Station, Vizianagaram, laid out in split plot design to evaluate the effect of integrated use of three types of organic manures in combination with three levels of inorganic fertilizers (NPK) with two varieties (Peddasamaand OLM 203) as main plots and 11 combinations of organic and inorganic fertilizers as sub plots. The grain and straw yields in little millet of both the varieties were significantly influenced by different fertilizer levels. The experimental results indicated that significantly highest grain and straw yields were recorded in the treatment 100% RDF+Neem cake @ 1 t ha-1. However it was on par with 75% RDF+Neem cake @ 1 t ha-1+Azospirillum @ 5 kg ha-1+PSB @5 kg ha-1, 100% RDF+Vermicompost @ 2 t ha-1, 75 % RDF+Vermicompost @ 2 t ha-1+Azospirillum @ 5 kg ha-1+PSB @ 5 kg ha-1 and 100% RDF+FYM @ 5 t ha-1+Azospirillum @ 5 kg ha-1+PSB @ 5 kg ha-1. While, maximum yields were observed with the OLM 203 variety of little millet. Moreover the uptake of macronutrients (NPK) was found to be the highest in the treatment 100% RDF+Neem cake @ 1 t ha-1 and micronutrients (Zn and Fe) in the treatment 100% RDF+Vermicompost @ 2 t ha-1. But the benefit cost ratio was found highest in 100% RDF treated plots followed by 100% RDF+FYM @ 5 t ha-1